The place of components in a conditional relationship in the system of causal relations - Bayalieva, G. Zh.; Bekmaganbetova, G. Sh. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2023)
In linguistics, the linguistic nature of the category of general compound sentences still requires deep recognition. Although it has been somewhat studied from the point of view of structural linguistics, there are still unresolved problems in determining the syntactic nature of complex structures in the relation of a condition. Based on the latest achievements in the syntax of a compound sentence, there is a clear need for a deeper functional and semantic consideration of this language category. This direction, of course, is distinguished by its novelty, scientific depth. In studies, characterized by the manifestation of an active subject – a person who knows the world, reflecting it through language, as a central figure, the linguistic phenomenon is studied from the point of view of the basic principles of its origin, or from the point of view of the principles of cognition of the world through thinking and the representation of these cognitive concepts through language. Of course, in modern science, all this is interpreted as such. In the in-depth knowledge of structural and semantic units in the conditioning relation, the most important thing is recognized as how these conditioning relations manifest themselves in nature and being-being and mental being inherent in humanity, and how they are expressed in language. This article provides for the consideration of conditional components as structures in a causal relationship. In the deepening recognition of structural and semantic units in the conditional relationship, it is recognized as the most important how this conditional relationship manifests itself in nature and creation-being and the mental being inherent in humanity, and how they are reflected in the language.